Detection limit of computed tomography for hepatoblastoma pulmonary metastases: Based on total resection using indocyanine green fluorescence - Yukihiro Tsuzuki; Norihiko Kitagawa; Masato Shinkai; Kyoko Mochizuki; Hidehito Usui; Kazuyoshi Okumura; Yuma Yagi; Akio Kawami; Masakatsu Yanagimachi; Kumiko Nozawa; Mio Tanaka (Elsevier, 2024)
Background: Intraoperative search for small pulmonary metastases of hepatoblastoma has been challenging; therefore, it has been difficult to determine the true detection limit of computed tomography (CT). This is the first report on the detection limit of CT for hepatoblastoma pulmonary metastases in patients who underwent resection of hepatoblastoma pulmonary metastases using indocyanine green fluorescence (ICGF). Methods: We retrospectively reviewed the CT images of patients who underwent resection of hepatoblastoma pulmonary metastases using ICGF between January 2013 and November 2021 at a single children's hospital and compared them with pathological findings. Results: Overall, 757 nodules were resected from 20 cases and 75 thoracotomies; 411 nodules were considered for the study and 286 were pathologically positive. The number of nodules classified by size in the pathological sections and the probability of CT detection were as follows: < 2 mm: CT-positive/pathology-positive, 43/144, 29.9 %; ≥ 2 and < 3 mm: 5/10, 50 %; ≥ 3 and < 4 mm: 20/27, 74.1 %; ≥ 4 and < 5 mm: 15/16, 93.8 %; ≥ 5 mm: 87/89, 97.8 %. Of 286 pathology-positive nodules, 59.4 % were CT-positive. With a cut-off value of 3 mm for tumor size, the proportion of CT-positive nodules was 92.4 %. Of 177 CT-positive nodules, 170 were pathologically positive. Conclusions: More than 90 % of nodules > 3 mm were detectable on CT, whereas less than 30 % of pathologically positive nodules < 2 mm could be detected. In children with hepatoblastoma, a CT-positive pulmonary nodule, even if minute, is likely to be malignant and metastasis should be suspected.